The PENGARUH KEMAJUAN OBJEK PARIWISATA TERHADAP TINGKAT KEMAMPUAN BAHASA INGGRIS MASYARAKAT MEDAN - Paula Melissa; Maurenta Bunga; Fathiha Malika Shakira (Universitas Harapan Medan, 2024)
Tourism is a travel activity carried out by an individual or a group of people from the place of origin to the destination. Tourism itself has an important influence in many aspects somewhere. Starting from the economic, social, educational, governmental or institutional aspects as well as in language. The language itself is one of the aspects that encourages local entertainment due to the large number of foreign tourists visiting the new tourist sites. The aim of the following research is to find out and observe the development of English-speaking skills of Indonesians in the tourism industry. The research method used is qualitative method by reviewing previous research (literature review). Previous research showed the results of significant English development of the Indonesian people due to the number of foreign tourists who come to travel and make the local people learn to know what they want to know from the tourist destination. This research is expected to be new information for tourists and other researchers.